2020
DOI: 10.1016/j.jneuroim.2020.577213
|View full text |Cite
|
Sign up to set email alerts
|

Loss of T cells influences sex differences in stress-related gene expression

Abstract: Deficiencies in the adaptive immune system have been linked to anxiety-like behaviours and stress reactivity. Mice lacking T lymphocytes through knockout of the T cell receptor (TCR) β and δ chains were compared to wild type C57Bl/6 mice. Central stress circuitry gene expression was assessed following repeated restraint stress. TCRβ−/−δ−/− mice showed an increased baseline plasma corticosterone and exaggerated changes in stressrelated gene expression after repeated restraint stress. Sexual dimorphic stress res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…In addition to a detailed map of the impact of T-cell deficiency on the microbial-metabolomic profile in the gut, this study demonstrated T-cell deficiency on development of the brain metabolome, with higher abundance of GABA, glycine, aspartate, acetate and glycerophosphocholine in the brains of TCR β–/–δ–/– mice across the lifespan. A role for T-cells in modulating brain development has been established, with previous studies showing changes in the volume of several brain regions in TCR β–/–δ–/– mice [ 13 ], paralleled by decreased anxiety-like behaviour, but elevated basal cortisol in TCR β–/–δ–/– mice [ 13 , 14 ]. Further, IL-17a released by meningeal γδ T-cells have also been shown to modulate anxiety-like behavior [ 2 ], and effect that may be mediated by microglia by inducing phagocytosis of neural progenitor cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to a detailed map of the impact of T-cell deficiency on the microbial-metabolomic profile in the gut, this study demonstrated T-cell deficiency on development of the brain metabolome, with higher abundance of GABA, glycine, aspartate, acetate and glycerophosphocholine in the brains of TCR β–/–δ–/– mice across the lifespan. A role for T-cells in modulating brain development has been established, with previous studies showing changes in the volume of several brain regions in TCR β–/–δ–/– mice [ 13 ], paralleled by decreased anxiety-like behaviour, but elevated basal cortisol in TCR β–/–δ–/– mice [ 13 , 14 ]. Further, IL-17a released by meningeal γδ T-cells have also been shown to modulate anxiety-like behavior [ 2 ], and effect that may be mediated by microglia by inducing phagocytosis of neural progenitor cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While not directly tested here, this is consistent with the changes in GABA in the present study in the frontal cortex, hippocampus and hypothalamus. Additional work is needed to demonstrate whether such alterations are the molecular basis for the abnormalities in anxiety-like behavior in TCR β–/–δ–/– mice [ 13 , 14 ]. In addition, the reported negative association between anxiety and fecal abundance of Muribaculaceae in humans [ 50 ] is intriguing and we suggest that this behavioral trait may be responsive to the changes in the microbiota of TCR β–/–δ–/– mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel with these observations, T-cell-deficient ( TCRβ-/-δ-/-) mice display abnormalities in both anxiety-like behaviour [ 16 ] and hypothalamic pituitary axis (HPA)-mediated stress response [ 17 ]. These behavioural changes were accompanied by a genotype-specific microbiome and metabolite signature, which was coincident with altered levels of neuroactive metabolites in the brain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%